Neovascularization, vascular mimicry and molecular exchange: The imaging of tumorous tissue aggressiveness based on tissue perfusion - Ferda, Jiří; Frölich, Matthias; Ferdová, Eva; Heidenreich, Filip; Charvát, Radim; Mírka, Hynek (European journal of radiology, 2023)
Angiogenesis in healthy tissue and within malignant tumors differs on many levels, which may partly be explained by vascular mimicry formation resulting in altered contrast material or different radiopharmaceuticals distributions. Failed remodulation results in changes in the molecular exchange through the capillary wall and those consequences affect the behavior of contrast agents and radiopharmaceuticals. One of the most indicative signs of malignant tissue is the increased permeability and the faster molecular exchange that occurs between the extracellular and intravascular spaces. Dynamic imaging can help to assess the changed microenvironment. The fast-distribution of molecules reflects newly developed conditions in blood-flow redistribution inside a tumor and within the affected organ during the early stages of tumor formation. Tumor development, as well as aggressiveness, can be assessed based on the change to the vascular bed development, the level of molecular exchange within the tissue, and/or indicative distribution within the organ. The study of the vascular network organization and its impact on the distribution of molecules is important to our understanding of the image pattern in several imaging methods, which in turn influences our interpretation of the findings. A hybrid imaging approach (including PET/MRI) allows the quantification of vascularization and/or its pathophysiological impressions in structural and metabolic images. It might optimize the evaluation of the pretreatment imaging, as well as help assess the effect of therapy targeting neovascularization; antiVEGF drugs and embolization-based therapies, for example.
Keywords: patologická angiogeneze; nádorové mikroprostředí; Perfusion; Neoplasms; kontrastní látky; magnetická rezonanční tomografie; Radiopharmaceuticals; Vascular mimicry; Perfusion imaging; Neovascularization; Pharmacokinetics; radiofarmaka; lidé; Contrast Media; Humans; Neovascularization, Pathologic; perfuze; nádory; Magnetic Resonance Imaging; Tumor Microenvironment